(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the relationship of hypoparathyroidism with patients of beta thalassemia major in a tertiary care hospital. Study Design: Cross-Sectional descriptive study. Place and Duration of Study: This study was conducted at the department of Pediatric medicine Hayatabad Medical Complex Peshawar from July to December 2021. Materials and Methods: A total number of 161patients with beta thalassemia fulfilling the inclusion criteria were included in the study. Patients were assessed through detail history, followed by clinical examination and laboratory investigations of serum level of calcium, phosphorus, haemoglobin, and serum parathyroid hormone. The data was recorded on a predesigned proforma. The data was analyzed by SPSS version 22. Results: Majority of thalassemic patients were male (70.7%) with a mean age of 12.79±1.80 years. Mean weight 19.39±4.88 kg. High serum ferritin level was found in 39.7% and 37.9% of patients had low parathyroid hormone levels. Hypoparathyroidism was non- significantly associated with gender and age; while significantly associated with hemoglobin, serum calcium, ferritin, phosphorus, weight and height in thalassemic individuals. Conclusion: Hypoparathyroidism is not an uncommon complication of beta thalassemia major necessitating early diagnosis and management of hypoparathyroidism in beta thalassemic patients.